The treatment of neurogenic bladder dysfunction in patient with spinal cord injury - Marković, Nataša (PONS - medicinski časopis, 2014)
Abstract: Neurogenic bladder dysfunction, resulted from demage to the neural structures in spinal lesion present a major problem for the patient, his environment and health care workers. Proper diagnosis of neurogenic bladder dysfunction allows you to implement appropriate treatment plan that will allow adequate emptying and prevention of complications that may endanger the patient's life . The evolution of spinal cord injuries can distinguish three phases: 1) spinal shock phase, 2) the recovery phase, 3) final phase. After spinal trauma bladder is affected mostly in two ways: 1) Spastic (reflex) bladder caused in lesion above voiding center (S2-S4 segments), 2) Flaccid (atonic) neuropathic bladder emerges in lesion at the voiding center (S2-S4) or below it, as well as lesions of the peripheral innervation of bladder, 3) Autonomic disreflection syndrome develops in patient with cervical or high thoracic spinal cord lesions, above the Th 1 segment, 4) Uninhibited neurogenic bladder develops in incomplete nerve pathway lesions in cerebral cortex, pyramidal pathway or in spinal cord – cerebral voiding control debilitate. The diagnosis of neurogenic bladder dysfunction is established by urodynamic examination, laboratory blood and urine findings as well as radiographic, computed tomography and nuclear magnetic resonance imaging of the spinal column. Bladder emptyng can be made by intermitetnt catheterization, Crede's procedure, suprapubic stimulation, smooth bladder muscle electrostimulation and by medications. The necessity of an Interdisciplinary approach to the treatment of these patients indicates all hardness in spinal cord injury patientes and consequent bladder dysfuncion. Key words: spinal cord injuries, urinary bladder; neurogenic, rehabilitation.